The Influence of Information Technology, Standard Operating Procedures, Employee Work Performance and Ethics on Public Satisfaction Using Government Services Regarding Passport Making, at the Ministry of Justice in Dili, Timor Leste - Barbosa, Francisco Nicolau B.; Ratnawati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of writing is to find out public satisfaction in public services that are influenced by technology, standard operating procedures, employee performance and communication ethics. Based on the results of the literature review, it can be concluded that information technology facilities variables affect community satisfaction variables, Standard Operating Procedures variables affect community satisfaction variables, employee work performance variables affect community satisfaction variables, and communication ethics variables affect community satisfaction.